Precise positioning in urban canyons : applied to the localisation of buried assets - Montillet, Jean-Philippe (2008)
The last decades have seen the applications related to Global Positioning Systems (GPS) flourishing in various and unrelated ways such as car navigation, electronic advertisement, military defense (e.g. missile tracking) ... etc. The increasing consumers interest in positioning market is also due to the recent coupling of mobile phone and GPS technologies which is deemed to kick-off the location based services market (LBS). The LBS market are electronic services for providing information that has been created, compiled, selected or filtered taking into consideration the current locations of the users or those of other persons or mobile objects. Analysts foresee that these services will open a new era of mass consumption market where all positioning technologies will play a key role. The level of positioning accuracy (e.g. 1 cm or 1 m) will be a service that the user may order from his mobile phone, laptop or other devices. In this background, the aim of the conducted research is to locate accurately buried pipes in built up areas using GPS and other positioning technologies. This work should be considered as an attempt to solve the general problem: positioning accurately everywhere and every time. Thus, the research work undertaken at the University of Nottingham Institute of Engineering Surveying and Space Geodesy (IESSG) focused on the integration of GPS with other existing technologies (e.g. signal from cellular networks). Algorithms are developed and then tested through simulations. The results showed that the integration of the GPS and GSM technologies may provide a position accuracy of a user no better than 20 m. The main issue is the lack of synchronisation between the two technologies. In a second part, a network of ground-based transceivers called LOCATA is introduced and studied in detail with statistics on the residual of the signal (e.g. multipath, fading) and the time series of the rover's position. Results were averaged on various environments (e.g. downs, urban canyons). The overall results showed that it is possible to locate the LOCATA rover better than 5 cm in 3D and better than 2 cm in 2D in both urban and open field scenarios. However some unwanted phenomena (interferences) were found which degraded the performances of this new technology (from a few centimetres to tens of centimetres). Finally, the LOCATA prototype was studied beyond its actual capabilities (at the time of writing this thesis) via simulations of the coupling with GPS technology. Results were extracted from a simulator and the statistics calculated from the data collected in the previous chapters. It gave a proof that the LOCATA-GPS technology may achieve the centimetre level in the urban canyons (in 3D).